Brahman as Śūnya: A Manifestation of the Formless Absolute in the Poetry of Bhima Bhoi (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The concept of Brahman holds a central position in Indian philosophical and religious traditions. Whereas, the Vedas and the Upanishads articulate Brahman as the ultimate metaphysical reality, the nineteenth-century Odia saint-poet Bhima Bhoi advocates a unique understanding of Brahman through the concept of śūnya (void). Based on the teachings of Mahima Dharma, Bhima Bhoi’s philosophy declares Brahman as Nirākāra (formless), Alekha (the indescribable), Nirguṇa (without attributes), and Śūnya (void). Here the concept of śūnya is not mere emptiness or negation of reality rather it is the infinite and ineffable ground of existence. Through his poems such as Stuti Chintāmaṇi, Brahma Nirūpaṇa Gītā, and Bhajanamālā, Bhima Bhoi presents a philosophy that envisions the formless Absolute through devotional spirituality, and universal compassion. This paper explores how Bhoi represents the idea of śūnya beyond its orthodox connotation of void or emptiness and interprets it as Brahman, the supreme, self-sufficient (pūrṇa), and all-permeating reality. The study also examines the philosophical fundamentals of notion by validating it with the Upanishadic notion of Brahman and the Buddhist concept of Śūnyatā.